2016
DOI: 10.1007/s11118-016-9585-7
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Differentiability for Solutions of Nonlinear Elliptic Equations

Abstract: We study nonlinear elliptic equations in divergence form(Formula presented.) When (Formula presented.) has linear growth in Du, and assuming that (Formula presented.) enjoys (Formula presented.) smoothness, local well-posedness is found in (Formula presented.) for certain values of (Formula presented.) and (Formula presented.). In the particular case (Formula presented.), G = 0 and (Formula presented.), (Formula presented.), we obtain (Formula presented.) for each (Formula presented.). Our main tool in the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 25 publications
2
38
0
Order By: Relevance
“…In this context see [6], [17], [10] and recently [13], [14] and [9]. The Sobolev dependence on x recently has been considered in [22], [1] and for obstacle problems in [16].…”
Section: A-priori Estimatesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context see [6], [17], [10] and recently [13], [14] and [9]. The Sobolev dependence on x recently has been considered in [22], [1] and for obstacle problems in [16].…”
Section: A-priori Estimatesmentioning
confidence: 99%
“…for some positive constants M 1 , M 2 , for an exponent p ∈ (1, +∞) and for every x ∈ Ω and ξ ∈ R n . The assumption usually considered in the mathematical literature for Lipschitz continuity of solutions is the Lipschitz continuity of f (x, ξ) with respect to x; more precisely, similarly to the Dirichlet integral in (1), the condition often assumed on the x−dependence is…”
mentioning
confidence: 99%
“…Now, we give a few comments on some results which are somehow connected to Theorem 1.1. In [2], see also [6], the authors obtain fractional regularity for the solutions of a broad class of degenerate equations with nonsmooth coefficients which generalize the p-Laplacian case. Indeed, by means of a difference quotient approach and by supposing that the data relies on Besov spaces it is proved that these solutions belong to a class of Besov spaces, locally see [2, Theorems 1.1-1.3].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in [33, 34] the second author observed that solutions admit a full additional derivative in the sense of Vμfalse(Dufalse)Wnormalloc1,2false(normalΩfalse) if the coefficients only possess a Sobolev type regularity, see also [12, 20, 21, 23]. Finally, both types of results were unified in [3, 11], where a fractional differentiability result in the scale of Besov spaces was established under the assumption that the coefficients admit a Besov‐type regularity property. For other higher differentiability results in the scale of Besov spaces, we refer to [13].…”
Section: Introductionmentioning
confidence: 99%